Global Atmospheric OCS Trend Analysis From 22 NDACC Stations. Issue 4 (8th February 2022) - Hannigan, James W.; Ortega, Ivan; Shams, Shima Bahramvash; Blumenstock, Thomas; Campbell, John Elliott; Conway, Stephanie; Flood, Victoria; Garcia, Omaira; Griffith, David; Grutter, Michel; Hase, Frank; Jeseck, Pascal; et al.
Abstract: Carbonyl sulfide (OCS) is a non‐hygroscopic trace species in the free troposphere and a large sulfur reservoir maintained by both direct oceanic, geologic, biogenic, and anthropogenic emissions and the oxidation of other sulfur‐containing source species. It is the largest source of sulfur transported to the stratosphere during volcanically quiescent periods. Data from 22 ground‐based globally dispersed stations are used to derive trends in total and partial column OCS. Middle infrared spectral data are recorded by solar‐viewing Fourier transform interferometers that are operated as part of the Network for the Detection of Atmospheric Composition Change between 1986 and 2020. Vertical information in the retrieved profiles provides analysis of discreet altitudinal regions. Trends are found to have well‐defined inflection points. In two linear trend time periods ∼2002 to 2008 and ∼2008 to 2016 tropospheric trends range from ∼0.0 to (1.55 ± 0.30%/yr) in contrast to the prior period where all tropospheric trends are negative. Regression analyses show strongest correlation in the free troposphere with anthropogenic emissions. Stratospheric trends in the period ∼2008 to 2016 are positive up to (1.93 ± 0.26%/yr) except notably low latitude stations that have negative stratospheric trends. Since ∼2016, all stations show a free tropospheric decrease to 2020. Stratospheric OCS is regressed with simultaneously measured N2 O to derive a trend accounting for dynamical variability. Stratospheric lifetimes are derived and range from (54.1 ± 9.7)yr in the sub‐tropics to (103.4 ± 18.3)yr in Antarctica. These unique long‐term measurements provide new and critical constraints on the global OCS budget. Plain Language Summary: Carbonyl sulfide (OCS) is the most abundant sulfur containing gas in the atmosphere. There are many sources and sinks of OCS and other sulfur species in the atmosphere but most other short lived sulfur species eventually are converted to OCS. It is important to quantify and understand OCS as it can be used to understand CO2 and the carbon cycle and also since it eventually is transported into the stratosphere where it maintains the sulfate aerosol layer at about 20 km into the atmosphere. This layer is very important for earth's energy balance and climate change. In contrast with earlier and less comprehensive reports, this global study from 22 observation stations worldwide, shows stratospheric OCS to be increasing north and south of the equator but decreasing near the equator and to be increasing in the troposphere to 2016 and decreasing since. The main drivers of OCS in the troposphere are the cumulative anthropogenic sources. Key Points: Global distribution of carbonyl sulfide (OCS) measured by NDACC solar absorption FTIR remote sensing Tropospheric trends in OCS are non‐monotonic globally, driven by anthropogenic emissions Longest term stratospheric trends are increasing outside of sub‐tropics